Response of chickpea to foliar supply of Hoagland’s solution under rain-fed condition - Javaid, Muhammad Mansoor; Waheed, Hasnain; Nazami, Nadeem; Ashraf, Muhammad; Li, Feng-Min; Tanveer, Asif (Semina. Ciências agrárias : revista cultural e científica da Universidade Estadual de Londrina, 2020)
Under rain-fed conditions, foliar application of nutrients is an efficient tool to eliminate the adverse effects of nutrients shortage and helpful to catch the maximum yield of any crop. Field experiments were executed to evaluate the effect of foliar spray of different strengths and application times of Hoagland’s solution on growth and yield characteristics of chickpea (Cicer arietinum L.) under rain-fed conditions. The treatments consisted of distilled water (control), 25, 50, and 75% strength of Hoagland’s solution sprayed at 7, 14, and 21 days after crop emergence (DACE) on two chickpea cultivars C-44 and CM-72. In terms of growth and yield, CM-72 showed superiority over C-44. The 75% strength of Hoagland’s solution showed an improvement of 32.9, 37.9, 35.3, 13.5, and 35% in dry weight, plant height, 100- seed weight, seed yield, and biological yield, respectively when sprayed at 21 DACE than distilled water. However, the lower strength (25%) of Hoagland’s solution produced similar results to distilled water. It is recommended that under rain-fed conditions chickpea cultivar CM-72 should be cultivated with a foliar supply of 75% strength of Hoagland’s solution at 21 DACE to obtain the maximum growth and yield.